KUNJUNGAN ANTENATAL CARE (ANC) PADA IBU HAMIL TRIMESTER III. APAKAH TINJAUAN ASPEK SOSIODEMOGRAFI MEMILIKI HUBUNGAN? - Idha Farahdiba; Ria Dwisafril Hairil; Sri Wahyuni; Sunaeni Sunaeni (Ensiklopedia of Journal, 2026)
One of the key measures in maintaining the health of mothers and fetuses during pregnancy is through regular prenatal care (ANC) visits conducted in accordance with health care standards. The objective of this study was to determine the relationship between sociodemographic factors and prenatal care (ANC) visits among pregnant women in their third trimester. A cross-sectional study design was used in this research. The study was conducted in the service area of the Pintu Langit Community Health Center. The study was conducted in April 2025. The study population consisted of all pregnant women in their third trimester registered at the Pintu Langit Community Health Center. The sample comprised 60 respondents. The sampling technique used was purposive sampling. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between family income (p-value: 0.042) and spousal support (p-value: 0.039) with ANC visits among pregnant women in the third trimester. It is recommended that Community Health Centers improve the accessibility and quality of health facilities to ensure that all pregnant women can undergo regular ANC checkups, including the provision of transportation or mobile clinic facilities, as well as the provision of subsidy programs or financial assistance for low-income families to reduce economic barriers to accessing ANC services.Keywords: Spousal Support, Pregnant Women, Family Income